Observations on the Cenomanian (Upper Cretaceous) ammonite Calycoceras (Calycoceras) obrieni Young, 1957 from Arizona and New Mexico - Cobban, W; Kennedy, W (1990)
Calycoceras (Calycoceras) obrieni Young, 1957 is revised on the basis of new collections from the upper Cenomanian Metoicoceras mosbyense zone of Arizona and New Mexico, and differences between it and C. (C.) naviculare (Mantell, 1822) are described. -Authors